Handbook of Visual Display Technology - Chen, Janglin; Cranton, Wayne; Fihn, Mark.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The second Edition of this remarkable Handbook offers readers a comprehensive overview of the science and technology of visual displays and the economic and human interface factors associated with the displays industry. Unique in the displays field, the Handbook serves as a single reference source with expert contributions from over 150 international display professionals and academic researchers. The Handbook contains extensive coverage of established and emerging display technologies, with discussion of physical principles, materials science and processing, device technologies and particular areas of application. The wide-ranging content also encompasses the fundamental science of light and vision, image acquisition and manipulation, display materials and processing techniques, TFTs, display driving and metrology. Prominence is given to liquid crystal displays, with later chapters devoted to emerging technologies including flexible displays, electrophoretic, electrowetting and electrofluidic displays and MEMS-based displays. Other sections consider 3D display solutions, projection systems and head-worn displays. Updated and extended throughout, major changes in the 2nd Edition include: • Significantly expanded section on touch and human-computer interaction • Reworked and updated chapters on OLEDs • Revised and extended coverage of mobile display technologies "...no engineering or science library can be without this book. It will be an asset for all companies engaged in display and display-related business." - extract from the Foreword of the 1st Edition by Dr M Anandan, President, Society for Information Display. .
From the Contents: Introduction -- Human Vision and Perception -- Introduction to Electronic Imaging -- Fundamentals of Driving -- Display Glass -- Inorganic Phosphors -- Liquid Crystal Fundamentals and Materials -- Colorant Transposition Displays -- 3D Display Fundamentals -- Mobile Displays -- Introduction to Display Metrology -- Introduction to Markets and Economics. .
Keywords: Electronics; Lasers; Optical materials; Semiconductors; Measurement; Measuring instruments; Electronics and Microelectronics, Instrumentation; Laser; Optical Materials; Semiconductors; Measurement Science and Instrumentation